Immunoglobulin classes, subclasses and complexes of IgG rheumatoid factor in rheumatoid plasma cells - Munthe, E. (1972)
The different immunoglobulin classes, IgG subclasses and types of light chains in plasma cells of thirty-four rheumatoid synovial membranes were studied. In some of these membranes a particular Ig class or IgG subclass was selectively concentrated, indicating local production of antibodies. Large amounts of plasma cells containing IgG were detected in all tissues. In contrast, many synovial membranes contained only few plasma cells with free rheumatoid factor activity, shown by binding of aggregated IgG. However, after pepsin digestion of tissue sections, greatly increased numbers of plasma cells were able to bind IgG. Our results indicated that the majority of plasma cells of rheumatoid tissues contained rheumatoid factors, but these were mostly blocked, due to intracellular complexing of IgG rheumatoid factors.